If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(9x + 9) + 2 = 3(15x) + -2 Reorder the terms: 5(9 + 9x) + 2 = 3(15x) + -2 (9 * 5 + 9x * 5) + 2 = 3(15x) + -2 (45 + 45x) + 2 = 3(15x) + -2 Reorder the terms: 45 + 2 + 45x = 3(15x) + -2 Combine like terms: 45 + 2 = 47 47 + 45x = 3(15x) + -2 Remove parenthesis around (15x) 47 + 45x = 3 * 15x + -2 Multiply 3 * 15 47 + 45x = 45x + -2 Reorder the terms: 47 + 45x = -2 + 45x Add '-45x' to each side of the equation. 47 + 45x + -45x = -2 + 45x + -45x Combine like terms: 45x + -45x = 0 47 + 0 = -2 + 45x + -45x 47 = -2 + 45x + -45x Combine like terms: 45x + -45x = 0 47 = -2 + 0 47 = -2 Solving 47 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -1+5r=9 | | 3(t-2)= | | 11p+21=-78 | | (7e-2)-(3e+6)=8 | | -2(5x-9)=5(-2x-8) | | 25=n-19 | | a(8+2b-6)= | | X^4+4x^3+20x^2=0 | | -8+-9=-8+-9 | | -6x^2-15=3x | | 25=4q+1 | | -10+7m=6m-3(n-2) | | -2x+8=-9x+2 | | (1/2)6c-122^10c | | -8p-3(6-5p)=2(p-3)-22 | | 18-(-1/3x)=-7 | | 7-5/2=4 | | 18--1/3x=-7 | | -6.3d=-8.19 | | 2(x-9)=-3 | | 2w-18=-14 | | 5x-21=3x+17 | | 4=z/6 | | 8/3f=104 | | 6.25x+5.25=40 | | 1.75x+0.30=4 | | 720/5=8640/k | | 14y-5(12.8)=22 | | 4x-15=3x-24 | | -7x=4y+16 | | y-3/5=71/2 | | 6.95x+5.95=40 |